REGULARIZATION OF NUMERICAL DIFFERENTIATION - Belaya, N. I.; Nechiporenko, N. A.; Bondarenko, L. A. (Radio Electronics, Computer Science, Control, 2024)
The algorithms of the approximation the derivative of the function given by table are given. Classic methods quasi-solution and discrepancy are used to numerical differentiation and lead the task to linear programming problems with special structure of distraction matrix, what allow us to decrease greatly computational complexity.